Impact of a patient-centered tool to reduce misconceptions about coronary artery disease and its treatment: The CAD roadmap - Laura D. Scherer; Grace A. Lin; Vinay Kini (Elsevier, 2024)
Objective: Health misinformation is common and can lead to harmful behaviors such as medication non-adherence. We assessed the impact of a novel patient educational tool focused on overcoming misconceptions among patients with coronary artery disease (CAD). Methods: We developed the CAD Roadmap, an educational tool aimed at explaining the disease trajectory and overcoming common disease misconceptions (such as that statin medications are not beneficial). We designed a pilot survey to assess patients' 1) CAD-related knowledge, 2) medication-taking behavior, and 3) acceptability of the Roadmap. Survey participants were recruited online. CAD knowledge scores were compared with repeated measures t-tests. Results: Among 114 patients with CAD (mean age 67 years, 63% male), average CAD-related knowledge was 79.0% pre-test and 89.7% after review of the CAD Roadmap (p < .001). After review of the Roadmap, 24% indicated they planned to take their medications more regularly, 93% agreed it was helpful in understanding medication benefits, and 77% felt more empowered to participate in medical decisions. Conclusion: The CAD Roadmap was evaluated positively, improved disease-related knowledge, and has the potential to improve adherence to treatments. Innovation: Unlike many other interventions, the CAD Roadmap is specifically designed to overcome common misconceptions to improve health behaviors.